Pemuridan : Pelayanan Efektif bagi Generasi Milenial di Gereja Protestan di Indonesia bagian Barat (GPIB) - August Corneles Tamawiwy (Theologia in Loco, 2022)
The future of the church does not depend on the younger generation, but the Lord Jesus Christ. This theological foundation leads the church—in this case GPIB—to a more effective and robust ministry for the Millennial generation through discipleship. This paper aims to show that without discipleship, every effort to reach Millennials to get involved in the church is efficient but has not been effective yet. Modifying worships and traditions to reach Millennials is a form of external transformation, while discipleship talks about internal transformation. Without internal transformation, efficient external transformation efforts have not been effective.